Mapping the Breaker Element of the Cuckoo Chromosome 4SshL of Wheat Wild Relative Aegilops sharonensis - Walter, Nicola L. (2025)
Wheat (Triticum aestivum), a global food staple, is threatened by climate change and the challenges that it brings. Additionally, its genome has become bottlenecked through millennia of selective breeding making it difficult to exploit new genes to contend with these challenges. Wild relatives of wheat are often utilised as a novel source of genetic diversity for wheat improvement. However, some wild relatives, including Aegilops sharonensis, contain gametocidal genes. These selfish genes ensure preferential transmission to offspring through inducing chromosomal breakages in gametes that lack them, resulting in agronomically unstable lines with shrivelled seeds and significant yield reductions. Due to their selfish nature, these genes are extremely difficult to remove, preventing useful germplasm from being used in breeding programmes. Here, molecular markers and skim-sequencing were used to characterise a gametocidal gene (Gc2)-containing translocation line, T4B-4Ssh. This line was shown to carry a 9 Mbp Chr. 4Ssh segment from Ae. sharonensis introgressed into wheat Chr. 4B. We developed and treated an F1 population of 4,800 seeds with 0.35% and 0.4% ethyl methane sulfonate (EMS), resulting in 67 M1 plants with potential loss of function in the Gc2 locus. Ten progeny from each M1 plant were genotyped to verify the normal segregation of the Chr. 4Ssh segment. Mendelian segregation was observed in two families, confirming mutations in the gametocidal locus. Two additional mutants demonstrated abnormal segregation patterns. Test crosses were also used to characterise the mutants. One mutant behaved as anticipated, while the others deviated from at least one expected outcome, indicating a more complex dynamic at play. Chromosome flow-sorting isolated the recombinant Chr. 4B-4Ssh from the wild-type T4B-4Ssh and mutant lines, prior to its sequencing. Single Nucleotide Variations (SNVs) were identified between the wild-type and the mutant lines, in the introgressed 4Ssh segment, using the MutChromSeq bioinformatics pipeline. The analysis identified two contigs within the Chr. 4Ssh segment that had mutations in two and three mutant lines, respectively. One contig aligned highly to an Ae. sharonensis basic helix-loop-helix gene (AE.SHARON.r1.4SG0366250), which may be considered a candidate for Gc2. However, collective consideration of the data generated in this study may indicate the existence of multiple genes responsible for gametocidal action. This research has taken great steps towards identification of the long sought after gametocidal gene, Gc2. Additionally, these mutant lines can be used to remove Gc2 from wheat-Ae. sharonensis introgression lines. This would allow valuable germplasm with potentially beneficial traits to be released to breeders, helping to improve food security in a more extreme and populated world.